2010
DOI: 10.1111/j.1523-1739.2009.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Threatened‐Species Focus on Conservation Planning

Abstract: Conservation efforts at local, regional, and global scales often focus on threatened species despite recent calls to adopt more equitable and potentially more economically rational approaches. Critics contend that conservation planning centered only on threatened species fails to deliver cost-efficient conservation outcomes. We explored how planning to preserve threatened mammal species would influence the efficiency and effectiveness of conservation investments in East Kalimantan, Indonesia. We found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…Specific status is the most recognised unit used by conservation organisations and international and/or national government agencies to determine conservation policy and actions (Drummond et al 2009;Farrier et al 2007;Posigham et al 2002). As resources (both human and financial) are limited, all conservation organisations need access to the most accurate systematic and taxonomic analyses of all taxa, threatened or not, including if possible their evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…Specific status is the most recognised unit used by conservation organisations and international and/or national government agencies to determine conservation policy and actions (Drummond et al 2009;Farrier et al 2007;Posigham et al 2002). As resources (both human and financial) are limited, all conservation organisations need access to the most accurate systematic and taxonomic analyses of all taxa, threatened or not, including if possible their evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, under scenario A (with a uniform representation target of 50%) the great part of gap species are low conservation interest ones, while under scenario B (differentiated targets) the gaps are mainly high conservation interest species. (Drummond et al 2009) also showed that an optimal solution differed in size and spatial configuration when using conservation goals favoring threatened or non threatened mammals.…”
Section: Resultsmentioning
confidence: 93%
“…Pressey and Logan (1998), Justus et al (2008) and Rondinini et al (2005) investigated the effect of varying the representation targets for individual features (e.g. 1, 5 or 10% of each feature's range) on the total area selected; Stewart et al (2007) examined how increasing individual representation targets (from 5 to 50%) over time affects longterm efficiency; Warman et al (2004), Carvalho et al (2010) and Drummond et al (2009) compared minimum set results and irreplaceability values with different set of representation targets (fixed target range an minimum viable population target for example) but results were confounded by the fact that more demanding targets affect the overall area obtained. Furthermore for Drummond et al (2009) and Carvalho et al (2010) the different targets were a peripheral aspect of their study and there is no in-depth analyses of how the results change and why when using different targets.…”
Section: Introductionmentioning
confidence: 99%
“…One often has to resort to simple measures of rarity as surrogates for extinction risk, whether they correlate with it or not (see section ''Need of protection''). There is some quantitative evidence that focusing on threatened species delivers benefits to non-threatened species close to what prioritization for all species would produce (Drummond et al 2010), which would reduce the amount of necessary data and computational effort.…”
Section: Lack Of Data and Surrogate Measuresmentioning
confidence: 96%